Synergistic Mechanism and Progressive Path of BIM Application in Historic Building Restoration: A Case Study of the Zhengyangmen Gate Tower Restoration Project - Wang, Yali (Scientific Journal of Technology, 2026)
To address the persistent challenge of “high-value recognition but low adoption intention” of Building Information Modeling (BIM) in the field of historic building restoration, this paper takes the Zhengyangmen Gate Tower restoration project in Beijing as a typical case and adopts a chain-of-evidence analysis method to systematically investigate the application mechanism of BIM in real engineering contexts. The study finds that the Zhengyangmen project has developed a synergistic closed loop of “environmental drivers → organizational innovation → technological empowerment → value recognition”. In this loop, policy support and public attention constitute the external driving forces, while organizational mechanisms and tool innovations form the responsive layer. This effectively mitigates the complexity of modeling non‑standard components, allowing the technical advantages of monitoring and early warning, nesting recording, and concealed craftsmanship preservation to materialize, thereby fostering value recognition among practitioners. Based on this, a three‑stage progressive promotion path of “digital documentation → process integration → lifecycle management” is constructed, and synergistic barrier‑breaking strategies are proposed from the technology, organization, and environment dimensions. This study provides an actionable engineering path for the systematic promotion of BIM technology in historic building restoration and offers practical guidance for the digital preservation of cultural heritage.